What Are the Applications of AI in Acute Care Settings? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2021)
Artificial intelligence (AI) is rapidly transforming healthcare, with a profound impact on acute care settings. The high-pressure, data-rich environments of ...
Keywords: AI in Emergency Medicine; Applications; Acute; Settings; Artificial Intelligence; Machine Learning; Deep Learning